Spot me: exploring experiences of body talk between personal trainers and their women clients - Gray, P.; Hurst, M.; Miles, E.; Ormerod, T. (Psychology of Sport and Exercise, 2026)
The gendered nature of UK gyms presents barriers to women's use of these spaces, where they often feel intimidated and self-conscious. Personal trainers (PTs) could be instrumental in creating less objectifying exercise environments for women. Exploring the actual interactions in personal training sessions and the dyadic experiences of these interactions could further understanding on how fitness professionals can improve women's experiences of exercise. The present study aimed to explore PTs' and their women clients' perspectives on their body-related interactions in their sessions. Six PT-client dyads from the UK took part in an observation-interview study. We used a novel method involving triangulating data from the personal training session itself, an interview with the PT and an interview with the client. Interactions from each dyad's recorded session were selected according to Objectification Theory and previous research in the personal training context. PTs and clients were then interviewed about their experiences of the selected interactions. Data from sessions and interviews were analysed using a critical realist reflexive thematic analysis. Four themes were generated and presented as composite vignettes: 1) A Body Alliance: How Relational History Creates a Safe Space, 2) Fluidity of Expertise Over the Client's Body, 3) When Body Talk is Lost in Translation, and 4) Strength in Reassurance. Findings suggest ways in which PTs can communicate in order to promote positive body image amongst their clients. This understanding provides insight into how to fitness professionals may reduce barriers to exercise for women, such that more women engage in exercise long-term.